Plasmon-assisted partially reduced TiO2 nanotube arrays for photoelectrochemical water splitting. (29th January 2020) - Qi, Weiting; Wang, Ning; Chen, Xingyu; Liang, Hongyan
Abstract: The partially reduced TiO2 nanotube arrays (R-TNTs) has been extensively investigated for photoelectrochemical (PEC) water splitting. However, the severe charge recombination and limited light harvesting hinder their photocurrent output. Herein, we present a strategy for prepared R-TNTs photoanode which can facilitate the charge separation and transfer simultaneously via formation of homojunction induced by the Ti 3+ self-doping and oxygen vacancies. Additionally, we deposited plasmonic Au nanoparticles on the R-TNTs surface to extend the light absorption in visible region and accelerate the charge transfer at the solid-liquid interface via plasmonic effect. As a result, in PEC water splitting experiments, the optimized Au modified R-TNTs (Au@R-TNTs) photoanode exhibits a photocurrent density of 1.64 mA·cm −2 with solar-to-hydrogen conversion efficiency up to 0.55% under AM 1.5 G illumination, 4-fold and 2-fold higher than that of the pristine TNTs, respectively. The photocatalytic activity in the visible region was dramatically improved. The exploration of interfacial carrier dynamics in homojuntion and the investigation of the synergistic effects of plasmonic enhanced photocatalyst provides guideline for designing solar energy harvesting devices.